Diamine oxidase-modified screen-printed electrode for the redox-mediated determination of histamine - Torre, Ricarda (2020)
Histamine is an important biogenic amine because of its role in immune responses and the regulation of physiological functions. It is also used as a food freshness indicator, so its maximum concentration in fish is legally regulated. Although several robust and sensitive methods for histamine detection are already available, it continues to be a challenge to develop simple and portable devices that allow rapid histamine screening at any point of the fish production chain. Thus, in this work, a simple, miniaturized and low-cost sensor for histamine analysis was developed. The construction of the sensor only takes 30 min and consists of the immobilization of the enzyme diamine oxidase on the surface of a screen-printed carbon electrode by cross-linking. The quantification of histamine was achieved by chronoamperometry (+ 0.2V,120 s) using hexacyanoferrate (III) as a redox mediator. This selective sensor provided a low limit of detection (0.97 mg L−1) and accurate and precise results and was successfully applied to the analysis of spiked tuna and mackerel extracts,obtaining recovery values of 99–100%. Moreover, the sensor shows good stability, maintaining 87.7% of its initial signalafter 35 days.